An Efficient Reconfiguration Method based on Standard Deviation for Series and Parallel Connected PV Arrays - Parlak, Koray Sener; Karakose, Mehmet (Ieee, 2014)
This paper proposes a new approach for reconfiguration of PV array. The proposed method is designed for series and parallel connected array which is widely used in practical. The developed control algorithm for this method uses panel irradiance values and decisions which adaptive panels connect to string of array. The algorithm considers irradiance level deviation from average value of each string of array with applying standard variation function. To prove the validity of the method, the simulations are performed in Matlab-Simulink. The simulation results show that the proposed method can enhance efficiency of array under partial shading condition.
3rd International Conference on Renewable Energy Research and Application (ICRERA) -- OCT 19-22, 2014 -- Milwaukee, WI
Keywords: partial shade condition; photovoltaic cells; reconfiguration methods